Effect of the quantity of dietary amino acids on egg production and layings by ceratitis capitata (Diptera, Tephritidae). - Ferro, M. I. [UNESP]; Zucoloto, F. S. [UNESP] (My University, 1990)
1. Diets containing different amounts of an amino acid mixture were tested in terms of egg production and layings by Ceratitis capitata. The amino acid composition of the diet was identical to that of casein. The other components of the diet were: 1.0 g agar, 0.8 g of a salt mixture, 0.8 g of a vitamin mixture, 1.6 g corn oil, 0.2 g Tween 80, 0.5 ml propionic acid, 90 ml distilled water and 0.5 ml of a 20% alcohol solution of nipagin. Diets containing 0.4, 0.8, 1.2, 1.6 and 2.0 g of an amino acid mixture per 100 ml diet and an amino acid-free control diet were used. The diets were made isocaloric by adding 12.4, 12.0, 11.6, 11.2 and 10.8 g sucrose, respectively. 2. The diet containing 1.2 g amino acids proved to be the best, leading to 6.84 egg layings per female per day and to production of 7.72 eggs per female per day.